2023
DOI: 10.3390/w15122224
|View full text |Cite
|
Sign up to set email alerts
|

The Sources of Sedimentary Organic Matter Traced by Carbon and Nitrogen Isotopes and Environmental Effects during the Past 60 Years in a Shallow Steppe Lake in Northern China

Abstract: The organic matter of lake sediment plays an important role in paleolimnological reconstruction. Here, we report a detailed study of organic matter components (Corg%, N%, δ13C, δ15N) in a dated sediment core of Hulun Lake in northern China. Multiple mixing models based on the stoichiometric ratios and stable isotopic compositions were applied to quantify the contributions of organic matter sources in lake sediment. The results show that the organic matter in the sediments from Hulun Lake mainly comes from terr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The paper "The Sources of Sedimentary Organic Matter Traced by Carbon and Nitrogen Isotopes and Environmental Effects during the Past 60 Years in a Shallow Steppe Lake in Northern China" [2] quantified the contribution of organic matter sources in the lake sediment via multiple mixing models based on the stoichiometric ratios and stable isotopic compositions. The results showed that the organic matter in the sediments from Hulun Lake mainly came from terrestrial organic matter: the proportion of terrestrial organic matter was more than 80%.…”
Section: Overview Of the Contribution Of The Special Issuementioning
confidence: 99%
See 2 more Smart Citations
“…The paper "The Sources of Sedimentary Organic Matter Traced by Carbon and Nitrogen Isotopes and Environmental Effects during the Past 60 Years in a Shallow Steppe Lake in Northern China" [2] quantified the contribution of organic matter sources in the lake sediment via multiple mixing models based on the stoichiometric ratios and stable isotopic compositions. The results showed that the organic matter in the sediments from Hulun Lake mainly came from terrestrial organic matter: the proportion of terrestrial organic matter was more than 80%.…”
Section: Overview Of the Contribution Of The Special Issuementioning
confidence: 99%
“…In this wide "Water Environment Pollution and Control" framework, this Special Issue aimed to provide important knowledge and lay a sound scientific foundation for the control and management of water environment pollution by studying the environmental behaviors and bioavailabilities of various pollutants. The thirteen articles in this Special Issue focusing on water environmental pollution and control are mainly divided into four categories: (1) the composition characteristics and environmental behaviors of the pollutants in the surface water (i.e., the Chinese lakes Ulansuhai [1], Hulun Lake [2], Tai Lake [3], Shahu Lake [4], and Russian Ancient lakes [5]); (2) the assessment of groundwater and aquifer interaction [6] and the sources, risks, and management of groundwater pollution [7]; (3) the impact of polluted water on human health [8][9][10]; and (4) the removal of pollutants in water [11][12][13].…”
Section: Introduction To the Special Issuementioning
confidence: 99%
See 1 more Smart Citation